ANALISIS FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA MAHASISWA PGSD MELALUI MATA KULIAH KEWIRAUSAHAAN - Raihanah Sari; Mahmudah Hasanah; Marya Ulfah; Fathul Jannah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Interest in entrepreneurship is the desire, interest and willingness to work hard or have a strong will to be independent or try to fulfill their needs without being afraid of the risks that will occur, and willing to learn from failure. Students are the forerunners of entrepreneurs who will build the country's economy. Education for students about entrepreneurship is needed to be able to grow interest in entrepreneurship, one of whic is through entrepreneurship courses. The aim of this research is to analyze the factors that influence students in entrepreneurship in terms of economics. This research is included in field research, namely research on cases that occur in the field or occur in PGSD students at Lambung Mangkurat University Banjarmasin. Determination of the subject in this study using purposive sampling, in order to obtain as many as 10 respondents. Data collection techniques in research are observation, interviews, and documentation. Based on the research conducted, the results show that the economic factors consist of capital and opportunities to meet economic needs. Economic factors are matters relating to the relationship with the economy that affect the entrepreneurial interest of PGSD students. Then related to interest, it can be seen that PGSD students are categorized as very interested in entrepreneurship, as evidenced by the majority of answers from interviews with students stating that they have a very big desire to run a business to become entrepreneurs because it promises quite a large profit.